Comparison between Continuous Subcutaneous Insulin Infusion versus Multiple Daily Insulin Injection Effects on the Quality of Life in Libyan Children with Type 1 Diabetes Mellitus - Sara Taeb,; Anwar Mersheg,; Khuloud Ajaj, (AlQalam Journal of Medical and Applied Sciences, 2025)
Type 1 diabetes mellitus (T1DM) is considered a chronic autoimmune disease. Since the 1970s, the continuous subcutaneous insulin infusion therapy (CSII) via pumps has been widely used in the management of T1DM in comparison to multiple daily insulin therapy (MDI). The present study aimed to compare the quality of life among pediatric age groups with type 1 diabetes mellitus who were treated by insulin pumps versus multiple daily injections. This study was a randomized trial carried out at the pediatric departments of Tripoli University Hospital and Children's Hospital, Tripoli, Libya, between September and November 2020. The Pediatric Quality of Life Inventory 3.0 Diabetes Module was used to assess the health-related quality of life of children with diabetes. This study was statistically managed via a computerized program of the Statistical Package for the Social Sciences version 21. A total of 54 Libyan children with T1DM were included in the study; 27 were treated by MDI, compared to 27 who were treated by CSII insulin pump. This study revealed that the health-related quality of life was better among the insulin pump group compared to the MDI group according to overall PedsQL dimensions’ comparison. Hemoglobin A1c readings were lower in the insulin pump group compared to the MDI group, 7.7% and 9.9%, respectively. In terms of diabetes symptoms and treatment problems, patients on CSII had better symptom control and fewer treatment barriers than the MDI group, some of which were statistically significant. Patients on insulin pumps had better communication with their health care providers. No difference had been identified between the two groups related to worry problems. This study concluded that the diabetic children who were treated by continuous subcutaneous insulin infusion “CSII” (insulin pump) had better health-related quality of life in almost all facets compared to multiple daily insulin injection “MDI”. Thence, early utilization of insulin pumps among diabetic children is recommended to improve health outcomes and reduce related adverse health outcomes.